2018
DOI: 10.1038/s41598-018-28769-0
|View full text |Cite|
|
Sign up to set email alerts
|

The tomato subtilase family includes several cell death-related proteinases with caspase specificity

Abstract: Phytaspases are Asp-specific subtilisin-like plant proteases that have been likened to animal caspases with respect to their regulatory function in programmed cell death (PCD). We identified twelve putative phytaspase genes in tomato that differed widely in expression level and tissue-specific expression patterns. Most phytaspase genes are tandemly arranged on tomato chromosomes one, four, and eight, and many belong to taxon-specific clades, e.g. the P69 clade in the nightshade family, suggesting that these ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 64 publications
(101 reference statements)
4
48
1
Order By: Relevance
“…Substitution of phytaspase cleavage sites precluded PS processing in vitro and inhibited systemin signalling in vivo, indicating that Asp-specific cleavage is required for signal biogenesis (Beloshistov et al 2017). However, which of the 12 tomato phytaspases (Reichardt et al 2018) is responsible for the production of L-systemin in vivo is still unclear. Also unclear is how prosystemin that lacks a secretion signal may meet with extracellular phytaspases.…”
Section: Different Types Of Ptm and Their Relevance For Peptide Biogementioning
confidence: 99%
“…Substitution of phytaspase cleavage sites precluded PS processing in vitro and inhibited systemin signalling in vivo, indicating that Asp-specific cleavage is required for signal biogenesis (Beloshistov et al 2017). However, which of the 12 tomato phytaspases (Reichardt et al 2018) is responsible for the production of L-systemin in vivo is still unclear. Also unclear is how prosystemin that lacks a secretion signal may meet with extracellular phytaspases.…”
Section: Different Types Of Ptm and Their Relevance For Peptide Biogementioning
confidence: 99%
“…Remarkably, no SBT3 clade family members were identified in N. benthamiana (Table 1, Supplemental Figures S2-S3). Three N. benthamiana subtilases may possess phytaspase activity based on the presence of an aspartic acid residue at the pro-domain junction as well as a histidine residue in the S1 pocket which is thought to bind to P1 aspartic acid (Supplemental Figures S2-S3, Reichardt et al, 2018).…”
Section: Pseudogenization Of Subtilases Is Consistent With a Contractmentioning
confidence: 99%
“…3). A phylogenetic analysis revealed that the five SBTs upregulated in intrusive cells all belong to Group 1 (Taylor and Qiu, 2017; Reichardt et al ., 2018) (Fig. 3), which contains many SBTs involved in biotic interactions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Group 1 SBTs also expanded in plants that undergo symbiosis with nitrogen-fixing bacteria. Group 1 SBTs also include many that are involved in plant defense (Taylor and Qiu, 2017; Reichardt et al ., 2018). These findings indicate that Group 1 SBTs may have evolved for biotic interactions, including parasitism.…”
Section: Discussionmentioning
confidence: 99%